Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Produk Es Teh Solo oleh Konsumen Mahasiswa Fakultas Ekonomi Universitas Pamulang - Dharma, Eka Adi; Bastian, M. Ibnu; Perdana, Adrinata; Yulianto, Yulianto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This Study aims to test and prove the influence of price and product quality on purchasing decisions for Solo iced tea products. The population in this study were students from the economics and business faculty at Pamulang University, management study program. This research used a sample of 51 respondents. The research method used is nonprobability sampling with purposive sampling technique. The results of the research show that the relationship between the independent variables, namely consumer perception and promotion, has a relationship with the dependent variable, namely purchasing decisions. From partial testing, the T test shows that price has no positive effect on purchasing decisions and the product quality variable shows a positive and significant effect on purchasing decisions. It can be concluded that the price variable has no effect and product quality has an effect on purchasing decisions. The coefficient of determination (R Square) is 0.374. Purchasing decisions can be explained by the price and quality of the product by 37.4%, while another 64.6% can be explained by other factors not examined in this research.